Literatur Review Analisis metode De-Militarized Zone (DMZ) dan Switch Port Security Sebagai Metode Keamanan Jaringan - Anggreni, Ni Komang Ayu Sri; Jasa, Lie (Majalah Ilmiah Teknologi Elektro, 2022)
Over time, the development of technology is very rapid.  It is certainly inseparable from the role of networks that can connect devices to be able to exchange information. Therefore, there is a need to secure computer networks to prevent cyber crime. The most commonly used attacks are Port Scanning and DoS (Denial Of Service). There are various ways to secure a computer network, one of which is by Switching port security. In addition to using Switch port security, the technique for securing network crimes is to use the De-Militarized Zone (DMZ). This study aims to compare network security performance with the Port security and DMZ methods where the tests obtained based on the review literature concluded that the use of the DMZ method carries out security by filtering requests by clients through firewall routers while Port security can provide security to the network by providing access to the server to registered ports only.